The soviet secret police. Ed. by S. Wolin and R.M. Slusser. [With contrib. of K. Shteppa [K.(F.) Šteppa], E.A. Andreevich [Andreevič], V.P. Artemiev [V.P. Artem'ev a.o.] (Praeger, 1957)
With bibliogr. and index.